A Ligand Field Molecular Mechanics Study of CO2‐Induced Breathing in the Metal–Organic Framework DUT‐8(Ni). Issue 11 (9th July 2019) - Melix, Patrick; Paesani, Francesco; Heine, Thomas
Abstract: Flexible metal–organic Frameworks (MOFs) are an interesting class of materials due to their diverse properties. One representative of this class is the layered‐pillar MOF DUT‐8(Ni). This MOF consists of Ni2 paddle wheels interconnected by naphthalene dicarboxylate linkers and dabco pillars (Ni2 (ndc)2 (dabco), ndc = 2, 6‐naphthalene–dicarboxylate, dabco = 1, 4‐diazabicyclo‐[2.2.2]‐octane). DUT‐8(Ni) undergoes a volume change of over 140% upon adsorption of guest molecules. Herein, a ligand field molecular mechanics (LFMM) study of the CO2 ‐induced flexibility of DUT‐8(Ni) is presented. LFMM is able to reproduce experimental and DFT structural features as well as properties that require large simulation cells. It is shown that the transformation energy from a closed to open state of the MOF is overcompensated fivefold by the host–guest interactions. Structural characteristics of the MOF explain the shape of the energy profile at different loading states and provide useful insights to the interpretation of previous experimental results. Abstract : The flexible metal–organic framework DUT‐8(Ni) exhibits an enormous volume change upon the adsorption of CO2 . The host–guest interactions of this process and its structural implications are studied using ligand field molecular mechanics. Host–guest interactions are identified as the primary trigger of flexibility. Together with long‐range effects, the understanding of DUT‐8(Ni) is improved.